EVALUASI STRATEGIS KUALITAS LEARNING MANAGEMENT SYSTEM (LMS) EDLINK MELALUI INTEGRASI EUCS, GAP ANALYSIS DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) PADA UNIVERSITAS PERTIWI - Kurniawan, Haris Dwi; Diana Ikasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of Edlink at Universitas Pertiwi supports learning activities, but user complaints indicate that system quality still requires evaluation. This study evaluates user satisfaction and improvement priorities by integrating End-User Computing Satisfaction (EUCS), Gap Analysis, and Importance-Performance Analysis (IPA), and compares perceptions of students and lecturers. A descriptive quantitative approach was applied using five EUCS dimensions—Content, Accuracy, Format, Ease of Use, and Timeliness—measured through importance and performance scores on a five-point Likert scale. Data from 140 respondents were analyzed using validity and reliability tests, mean scores, Gap Analysis, IPA, normality testing, and an independent-samples t-test. The overall performance score was 4.316 and categorized as very satisfied. Timeliness obtained the highest performance mean (4.400), while Accuracy obtained the lowest (4.247). The largest negative indicator gap occurred on A03 (−0.107), whereas IPA placed E03, ease of finding needed features, in Quadrant I as the main improvement priority. The t-test showed a significant difference between students and lecturers (p=0.005), with mean satisfaction of 4.372 and 4.175, respectively. The integrated findings support recommendations for navigation improvement, data accuracy controls, notification reliability, and differentiated user support.